The lived experiences of chronic pain among immigrant Indian-Canadian women: A phenomenological analysis. Issue 3 (1st September 2020) - Mustafa, Nida; Einstein, Gillian; MacNeill, Margaret; Watt-Watson, Judy
ABSTRACT: Background : Chronic pain is a growing public health concern affecting 1.5 million people in Canada. In particular, it is a concern among the expanding immigrant population, because immigrant groups report higher pain intensity than non-immigrants. In 2011, the Indian population became the largest visible minority group and continues to be the fastest growing. Though the prevalence of chronic pain among Canadian Indians is unknown, research has found a higher prevalence among Indian women than men in India, Malaysia, Singapore, and the United Kingdom, with women reporting more severe pain. An understanding of how pain is experienced by this particular group is therefore important for providing culturally sensitive care. Aims: This study explores the lived experiences of chronic pain among immigrant Indian women in Canada. Methods: Thirteen immigrant Indian women participated in one-on-one interviews exploring daily experiences of chronic pain. Results: Using thematic analysis informed by van Manen's phenomenology of practice, four themes emerged: (1) the body in pain, (2) pain in the context of lived and felt space, (3) pain and relationships, and (4) pain and time. Women revealed that their experiences were shaped by gender roles and expectations enforced through culture. Specifically, a dual gender role was identified after immigration, in which women had to balance traditional household responsibilities of family labor and care alongside employment outside the home, exacerbating pain. Conclusions: This research uncovers the multifaceted nature of chronic pain and identifies factors within the sociocultural context that may place particular groups of women at greater risk of living with pain.